Taxing E-Commerce in the Post-Wayfair World - David Gamage; Darien Shanske; Adam Thimmesch (Washington University Journal of Law & Policy, 2019)
This article analyzes the implications of the Wayfair decision and considers the steps state governments should take in reaction to it. In Wayfair the Supreme Court overruled its decision of Quill and held a state may collect sales taxes from foreign vendors who lack physical presence in the state as long as the vendor still has sufficient contacts with the forum state. Thus the authors consider a number of steps states should take to ensure their tax regime complies with the minimum requirements of the dormant commerce clause. Specifically the authors – relying on the courts opinion and other sources – recommend: 1) simplifying tax regimes – potentially by joining the Streamlined Sales and Use Tax Agreement; 2) reimbursing compliance costs for smaller vendors; 3) offering free compliance software; 4) ensuring their sales tax regime has sufficiently high de minimis thresholds to alleviate dormant commerce clause concerns; 5) maintaining similar thresholds for corporate income tax nexus purposes; 6) applying the same standards to major marketplaces as well as direct sales; and 7) taking steps to mitigate the chances citizens will switch to buying from foreign vendors.
Keywords: Tax; SALT; State and local taxes; Tax law; South Dakota v. Wayfair; Inc. 138 S. Ct. 2080 (2018); Quill Corp. v. North Dakota; 504 U.S. 298 (1992); Use tax; Sales tax; E-commerce; Dormant commerce clause; Interstate commerce